The land-river interface: a conceptual framework of environmental process interactions to support sustainable development - Grabowski, Robert C.; Vercruysse, Kim; Holman, Ian P.; Azhoni, Adani; Bala, Brij; Shankar, Vijay; Beale, John; Mukate, Shrikant; Poddar, Arunava; Peng, Jian; Meersmans, Jeroen (Springer, 2022)
Rivers and their surrounding lands are focal points of human development in the landscape. However, activities associated with development can greatly affect river processes, causing significant and often unintended environmental and human impacts. Despite the profound and varied environmental impacts that development-related alterations cause through hydrological, geomorphic, and ecological processes, they are not widely acknowledged outside of river management and affect resource availability and hazard exposure to people. In this paper, we propose a novel, interdisciplinary conceptual framework of river–land process interactions to support sustainable management and development. We introduce the term ‘land–river interface’ (LRI) to describe areas of the landscape in which river processes affect land, vegetation, and/or fauna, including humans, directly or indirectly. The multiple links between LRI processes and factors at the river basin, valley, and river channel (i.e. reach) scale are synthesized and a conceptual zonation of the LRI based on the process is proposed to serve as a framework to understand the impacts of human activity. Three examples of development-related activities (urbanization, dams and aggregate mining) illustrate how alteration to the form and functioning of river basins, valleys, and channels cause a range of impacts to be propagated throughout the landscape, often spatially or temporally distant from the activity. The diversity and severity of these impacts on the environment and people underscore the need to incorporate river processes, as represented in the LRI concept, into broader environmental management to better anticipate and mitigate negative impacts and maximize positive outcomes to deliver the benefits of sustainable development across society.
Keywords: Fluvial geomorphology; Urbanization; Dams; Sand mining; Integrated water resource management